Pathophysiology of primary open-angle glaucoma from a neuroinflammatory and neurotoxicity perspective: a review of the literature - Evangelho, Karine; Mogilevskaya, Maria; Losada-Barragan, Monica; Vargas-Sanchez, Jeinny Karina (International ophthalmology, 2019)
Purpose Glaucoma is the leading cause of blindness in humans, affecting 2% of the population. This disorder can be classified into various types including primary, secondary, glaucoma with angle closure and with open angle. The prevalence of distinct types of glaucoma differs for each particular region of the world. One of the most common types of this disease is primary open-angle glaucoma (POAG), which is a complex inherited disorder characterized by progressive retinal ganglion cell death, optic nerve head excavation and visual field loss. Nowadays, POAG is considered an optic neuropathy, while intraocular pressure is proposed to play a fundamental role in its pathophysiology and especially in optic disk damage. However, the exact mechanism of optic nerve head damage remains a topic of debate. This literature review aims to bring together the information on the pathophysiology of primary open-angle glaucoma, particularly focusing on neuroinflammatory mechanisms leading to the death of the retinal ganglion cell. Methods A literature search was done on PubMed using key words including primary open-angle glaucoma, retinal ganglion cells, Müller cells, glutamate, glial cells, ischemia, hypoxia, exitotoxicity, neuroinflammation, axotomy and neurotrophic factors. The literature was reviewed to collect the information published about the pathophysiologic mechanisms of RGC death in the POAG, from a neuroinflammatory and neurotoxicity perspective. Results Proposed mechanisms for glaucomatous damage are a result of pressure in RGC followed by ischemia, hypoxia of the ONH, and consequently death due to glutamate-induced excitotoxicity, deprivation of energy and oxygen, increase in levels of inflammatory mediators and alteration of trophic factors flow. These events lead to blockage of anterograde and retrograde axonal transport with ensuing axotomy and eventually blindness. Conclusions The damage to ganglion cells and eventually glaucomatous injury can occur via various mechanisms including baric trauma, ischemia and impact of metabolic toxins, which triggers an inflammatory process and secondary degeneration in the ONH.